Instructional Leadership Skills of School Heads and Its Relation to the Self-Efficacy of Elementary Teachers in Castillejos District - Battad, Jovelle L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study focused on the instructional leadership skills of School Heads and their relation to the self-efficacy of elementary teachers in all schools in Castillejos District, Division of Zambales. The data gathered were treated using Mean, Standard Deviation, One-Way ANOVA, and Pearson r. Overall, the teacher’s perception of instructional leadership skills of the school heads in terms of being Resource Providers, Instructional Resources, Communicators, and Visible Leaders got a descriptive rating of “Always”. Generally, teacher’s perceived self-efficacy in terms of Encouraging Student Engagement, Instructional Strategies, and Classroom Management stipulated a descriptive rating of “A Great Deal”. There is a significant difference in the school head’s instructional leadership skills when grouped according to their age, number of years as school head, and number of seminars/trainings attended related to instructional leadership. There is no significant difference in the school head’s instructional leadership skills when grouped according to their sex and highest educational attainment. Lastly, the school head’s instructional leadership is significantly correlated to teachers’ self-efficacy. Based on the findings and conclusions, the following are recommended: School heads should continue their professional growth and development by enrolling in Graduate School. Likewise, attend more training related to instructional leadership. School heads should strengthen their instructional leadership skills.